Clinicopathological characteristics of colorectal carcinoma complicating ulcerative colitis. Issue 10 (October 1994) - Connell, W R; Talbot, I C; Harpaz, N; Britto, N; Wilkinson, K H; Kamm, M A; Lennard-Jones, J E
Abstract : This study examined three features associated with colorectal carcinoma complicating ulcerative colitis: (a) the distribution of 157 cancers in 120 patients with ulcerative colitis treated at St Mark's Hospital between 1947 and 1992; (b) the frequency at which dysplasia was found at a distance from the tumour in 50 total proctocolectomy specimens in which an average of 27 histology blocks were reviewed, and (c) the five year survival rate according to Dukes's stage and participation in a surveillance programme. Of 157 carcinomas, 88 (56%) occurred in the rectosigmoid, 19 (12%) in the descending colon or splenic flexure, and 50 (32%) in the proximal colon. Among the 120 patients, the rectum or sigmoid colon contained cancer in 81 (67.5%). Dysplasia was detected in 41 of 50 reviewed proctocolectomy specimens (82%). Dysplasia distant to a malignancy occurred in 37 (74%); two were classified indefinite, probably positive, 19 were low grade, and 16 were high grade; in 18 specimens there was an elevated dysplastic lesion. Survival was related to the Dukes's stage: about 90% of patients with Dukes's A or B cancer were alive at five years. The five year survival of 16 patients in whom cancer developed during surveillance was 87% compared with 55% of 104 patients who did not participate in surveillance (p = 0.024).